Lipoprotein from Proteus mirabilis. - Katz, E (1978)
The biosynthesis of a Proteus mirabilis outer membrane protein of molecular weight of approximately 7,000 was found to be relatively resistant to puromycin and rifampin, as is the case for the Escherichia coli liporotein. Furthermore, the existence of the lipoprotein in P. mirabilis was indicated by a comparison of the amino acid compositions of the purified free and bound forms of this protein with those of the E. coli free and bound lipoproteins.